The Imaginationless Generation: Lessons from Ancient Culture on Regulating New Media - Goltz, Nachshon; Dowdeswell, Tracey (BRILL, 2019)
The Imaginationless Generation is a pioneering attempt to present a new theory for a new age of digital media. The authors follow the theory's insights and predictions to offer a new perspective on one of the most burning questions of our time - how to protect children online.